Validity of business excellence models : a conceptual and empirical analysis : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Technology at Massey University, Palmerston North, New Zealand - Jayamaha, Nihal P. (Massey University, 2008)
The validity of three key Business Excellence (BE) models used in the Asia Pacific—the Australian Business Excellence Framework (Australia), the Baldrige Criteria for Performance Excellence (New Zealand) and the Singapore Quality Award Criteria (Singapore)—was examined from a conceptual as well as a predictive standpoint. Unlike in many past studies, in this study the validity of the measurement criteria stipulated in BE models have been directly assessed. The conceptual validity of the three BE models was studied through a generic theoretical model using the partial least squares-based structural equation modelling (PLSBSEM) method. Apart from measurement validity, the strengths of the hypothesised causal relationships between the constructs of the BE models and their practical implementations were also examined under conceptual validity. The predictive validity of the three BE models was examined through linear predictive models involving enablers—being measures in BE models that cover what organisations actually do in order to achieve business outcomes—as predictors and business outcomes as responses. Alongside predictive validity, the reasonableness of the stipulated weights of the enablers was also examined. Other empirical and pragmatic inquiries covered in this study included: (a) a study of the effect of “industry attractiveness” on financial and market performance, and (b) a study of the relationship between BE constructs and “national cultural dimensions”. Results revealed that although the three BE models fulfilled the basic requirements of measurement validity, against more stringent criteria such as those used in psychometrics, they showed low levels of validity. The possible reasons for this were examined and the ways of overcoming the shortcoming were suggested. The generic theoretical model was found to be statistically significant across all three settings: Australia, New Zealand and Singapore. As regards predictive validity, it was observed that enablers appear to be good predictors of business outcomes (thus establishing predictive validity) although there was scope for improvement of the existing weighting scheme of the enablers. This study is important because many organisations in the region use BE models with the expectation of improving their performance in key results areas and hence there is a need to demonstrate that the BE models are based on sound concepts.
Keywords: Business outcomes; Enablers; Measurement validity; Fields of Research::350000 Commerce, Management, Tourism and Services::350200 Business and Management